USULAN PERBAIKAN TATA LETAK PENYIMPANAN GUDANG BARANG ATK BERDASARKAN KEBIJAKAN DEDICATED STORAGE DENGAN MENGGUNAKAN ALGORITMA GREEDY DI KANTOR POS ASIA AFRIKA BANDUNG - Septiona, Septiona; Mulyati, Erna; Purnomo, Agus (JURNAL ADMINISTRASI KANTOR, 2023)
Efficient storage in a stationery warehouse plays an important role in ensuring the availability and accessibility of products needed. A non-optimal arrangement in warehouse storage can result in wasted time due to slow search for items and lack of space for new items. This article discusses the proposed improvement of the storage layout of the stationery warehouse based on the "Dedicated Storage" policy with the application of the Greedy algorithm. The "Dedicated Storage" policy refers to the concept of allocating fixed storage locations for specific groups of goods. In this proposal, the Greedy algorithm is used to design a more efficient warehouse storage layout. The Greedy algorithm prioritizes decision-making based on the best local criteria at each step, in the hope of achieving an adequate global solution. In this context, the Greedy algorithm is applied to determine the optimal storage location based on the Dedicated Storage policy. The steps taken in this research include: (1). Data collection of stationery items to be stored, including attributes such as size, frequency of demand, and category. (2). Formation of groups of goods based on certain categories or attributes. (3). Application of the Greedy algorithm to determine the optimal storage location for each group of goods. And (4). Evaluation of the performance of the new layout based on parameters such as item search time and space utilization efficiency.  The results of this study are expected to provide practical guidance for improving the storage layout of the stationery warehouse. By adopting the Dedicated Storage policy and utilizing the Greedy algorithm, it is expected that the warehouse will have a more structured and efficient layout. This can reduce search time, increase productivity, and optimize space usage. In addition, this proposed concept can also be adapted in the context of storing goods in various types of warehouses or other storage facilities.   Keywords: Improvement Proposal, Warehouse Layout, Storage Management, Dedicated Storage Policy.